Journal of Instrumentation - Naumenko physicist senior research fellow, Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences; Potylitsyn Russian physicist Professor of the TPU; Shevelev physicist research engineer of Tomsk Polytechnic University; Karataev physicist head of the laboratory of Tomsk Polytechnic University; Shipulya physicist Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences; Bleko physicist engineer-researcher of Tomsk Polytechnic Universit (2018)
Electron beams of most accelerators have a bunched structure and are synchronized with the accelerating RF field. Due to modulation of the electron beam with frequency v[RF] one can expect to observe resonances with frequencies vk= kЁv[RF] in radiation spectrum generated via any spontaneous emission mechanism (k is an integer and the resonance order). In this paper we present the results of spectral measurements of coherent transition radiation (CTR) generated by an electron bunch train from the Tomsk microtron with v[RF]=2.63GHz in the spectral frequency range from 8 to 35 GHz. We also measured the spectrum of coherent diffraction radiation and demonstrated that the observed spectra in both cases consist of monochromatic lines. For spectral measurements the Martin-Puplett interferometer with spectral resolution of 800 MHz (FWMH) was employed. Using a waveguide frequency cut-off we were able to exclude several spectral lines to observe higher resonance orders of up to k=7.